Semiotic systems, cognitive artefacts, Umwelt – a contribution to Information Design - Queiroz, João (InfoDesign, 2011)
The development and analysis of ‘environments, niches and semiotic landscapes’ may accurately characterize the activities of Information Design. This introductory paper explores this perspective through the notions of ‘cognitive and semiotic artifacts’, ‘semiotic system’ and Umwelt. It is presented from within a theoretical field, relating semiotic processes, cognitive technologies and artifacts, and it is based on empirical treatment in Behavioral Ecology, Ethology, and Cognitive Semiotics. [ Download ]